High Precision Dual Frequency Doppler Lidar Based on Monolithic Integrated Two-Section DFB Lasers - Zuye Lu; Yunshan Zhang; Jie Zeng; Lianyan Li; Bocheng Yuan; Yuechun Shi; Jilin Zheng; Zijun Shang; Rulei Xiao; Tao Fang; Xiangfei Chen (IEEE Photonics Journal, 2019)
A dual-frequency Doppler Lidar (DFDL) with high precision utilizing a monolithic integrated two-section DFB laser as the dual-frequency light source is proposed and experimentally demonstrated. The DFDL can be realized with smaller size using the monolithic integrated two-section DFB laser which is fabricated by the reconstruction-equivalent-chirp (REC) technique with high precision and low fabrication cost. The range of the measured speed is from 13.62 μm /s to 1.56 m/s, which covers 6 orders of magnitude. The largest relative error of the DFDL system is 3.16%. The DFDL system has an excellent resolution of 1.95 μm/s, which is suitable to detect micro speed changes.